2017
DOI: 10.1016/j.rbmo.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rates in various subgroups of poor ovarian responders fulfilling the Bologna criteria

Abstract: The European Society of Human Reproduction and Embryology published Bologna criteria to generate a definition of poor ovarian responders (PORs). However, there are few data on whether PORs are homogenous for ovarian response or live birth rates (LBRs). In this retrospective study, 821 patients fulfilling Bologna criteria and undergoing intracytoplasmic sperm injection were stratified into four groups: Group A: female age ≥40 with a previous poor response (cycle cancelled or ≤3 oocytes) (105 patients, 123 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 17 publications
6
34
0
Order By: Relevance
“…In contrast with the aforementioned findings, our results are in line with those described by Bozdag et al, who demonstrated LBR of 2.3-8.7% per started IVF cycle in BC PORs, with "young proven" PORs having the most favorable reproductive outcomes (12). Nonetheless, our primary endpoint was cumulative LBR, which is a more relevant clinical outcome, while Bozdag et al assessed only fresh LBR (12).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast with the aforementioned findings, our results are in line with those described by Bozdag et al, who demonstrated LBR of 2.3-8.7% per started IVF cycle in BC PORs, with "young proven" PORs having the most favorable reproductive outcomes (12). Nonetheless, our primary endpoint was cumulative LBR, which is a more relevant clinical outcome, while Bozdag et al assessed only fresh LBR (12).…”
Section: Discussionsupporting
confidence: 90%
“…However, there is evidence that even within the BC population, a significant degree of heterogeneity still persists (11). Indeed, several patterns or subgroups of PORs can be distinguished within the BC based on possible combinations of risk factors, ORT results, and IVF attempts (11)(12)(13). These subpopulations clearly encompass diverse baseline characteristics and the prognostic potential of these naturally emerging subgroups, as well as their reproductive outcomes, remain unclear and urge further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The control group, which was matched for age and the number of previous failed IVF cycles, showed a much poorer ongoing pregnancy rate of 6% per cycle. The control group pregnancy rates are similar to those reported in other large studies of poor responders at 2%-8% per cycle (Bozdag et al, 2017;La Marca et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…The marker of success according to the POSEIDON stratification is the number of retrieved oocytes required to obtain at least one euploid embryo for transfer in each individual patient [7]. Some studies evaluated live birth rates in different subgroups of POR patients fulfilling the Bologna criteria and found similar live birth in different subgroups [10,1,11,12]; furthermore, these studies reported that the independent significant variables related to the live birth rate were women' age [10,11] and the number of oocytes retrieved [12]. Only one study compared the live birth rates in different subgroups of POR patients on the basis of the POSEIDON classification and reported that the live birth rates (LBR) were significantly higher in POSEIDON group 1 and 2 compared with the other groups; the authors assumed that good ovarian reserve in these groups lead to a better ART outcome [9].…”
Section: Poseidon (Patients-oriented Strategies Encompassing Individumentioning
confidence: 99%